The role of perioperative sodium bicarbonate infusion affecting renal function after cardiothoracic surgery - Turner, Katja R.; Fisher, Edward C.; Hade, Erinn M.; Houle, Timothy T.; Rocco, Michael V. (Frontiers in Pharmacology, 2014)
Cardiac surgery associated acute kidney injury (CSA-AKI) is associated with poor outcomes including increased mortality, length of hospital stay and cost. The incidence of acute kidney injury (AKI) is reported to be between 3-30% depending on the definition of AKI. We designed a multicenter randomized controlled trial to test our hypothesis that a perioperative infusion of sodium bicarbonate during cardiac surgery will attenuate the postoperative rise in creatinine indicating renal injury when compared to a perioperative infusion with normal saline. An interim analysis was performed after data was available on the first 120 participants. A similar number of patients in the two treatment groups developed acute kidney injury (AKI), defined as an increase in serum creatinine the first 48 hours after surgery of 0.3 mg/dl or more. Specifically 14 patients (24%) who received sodium chloride (SC) and 17 patients (27%) who received sodium bicarbonate (SB) were observed to develop AKI post surgery, resulting in a relative risk of AKI of 1.1 (95% CI: 0.6-2.1, chi-square p-value=0.68) for patients receiving SB compared to those who received SC . The data safety monitoring board for the trial recommended closing the study early as there was only a 12% probability that the null hypothesis would be rejected. We therefore concluded that a perioperative infusion of sodium bicarbonate failed to attenuate the risk of CSA-AKI.